2006
DOI: 10.1111/j.1463-1326.2006.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of high density lipoprotein apolipoprotein A‐I and cholesteryl ester in insulin resistant dog: a stable isotope study

Abstract: Lower HDL-CE selective uptake suggests that RCT is impaired in obese insulin resistant dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In the current study, greater APO-A1 concentrations were detected in dogs with ORMD as observed in proteomic analysis and verified by a specific assay. These results are consistent with those reported by Briand et al [ 24 ] who, in a stable isotope study, observed increased APO-A1 production in insulin resistant dogs.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, greater APO-A1 concentrations were detected in dogs with ORMD as observed in proteomic analysis and verified by a specific assay. These results are consistent with those reported by Briand et al [ 24 ] who, in a stable isotope study, observed increased APO-A1 production in insulin resistant dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Insulin-resistant dogs have high triglyceride and nonesterified fatty acid (NEFA) levels, as well as low highdensity lipoprotein (HDL) cholesterol levels, which are the most common abnormalities in insulin-resistant humans [11]. The impact of insulin resistance was investigated on HDL metabolism in this animal model demonstrating a decrease in reverse cholesterol transport intensity [12]. Studies in insulin-resistant humans have shown that hypertriglyceridemia is related to a high very low-density lipoprotein (VLDL) production and delayed VLDL catabolism [13].…”
mentioning
confidence: 99%